2012
DOI: 10.1603/ec11184
|View full text |Cite
|
Sign up to set email alerts
|

Host Association of Spodoptera frugiperda (Lepidoptera: Noctuidae) Corn and Rice Strains in Argentina, Brazil, and Paraguay

Abstract: Spodoptera frugiperda (J.E. Smith) is composed of two genetically distinct strains, the so-called corn strain and the rice strain. Whether the two strains differ in their host use is unclear, because laboratory experiments have not been able to show consistent host performance or preference differences between them, and field studies showed high rates of hybridization, as well as some degree asymmetric host use. To determine the distribution of the two strains and their association with host plants, we collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 57 publications
(99 reference statements)
3
95
0
5
Order By: Relevance
“…These results are similar to the highest values of fertilization obtained in experiments using S. frugiperda when various couples were maintained in each cage (N= 25) (Milano et al, 2008), and are higher than those obtained by Juárez et al (2012), who evaluated different populations of the same species using only one couple per cage. (Kaplan-Meier) and confidence intervals of Spodoptera eridania moths emerged from small, medium-sized and large pupae.…”
Section: Discussionsupporting
confidence: 85%
“…These results are similar to the highest values of fertilization obtained in experiments using S. frugiperda when various couples were maintained in each cage (N= 25) (Milano et al, 2008), and are higher than those obtained by Juárez et al (2012), who evaluated different populations of the same species using only one couple per cage. (Kaplan-Meier) and confidence intervals of Spodoptera eridania moths emerged from small, medium-sized and large pupae.…”
Section: Discussionsupporting
confidence: 85%
“…frugiperda occurred in two races, a ‘rice strain’ (R strain) and a ‘corn strain’ (C strain) 10 ; the former is thought to preferentially feed on rice and various pasture grasses and the latter on maize, cotton and sorghum, although this may be geographically variable, e.g. this is not consistent in Argentina 11 . The strains are morphologically identical, but can be distinguished using DNA barcodes 12 which show two distinct clusters 13 that may have diverged 2 myr ago and now have a mean sequence divergence of 2.09% 14 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, three possible prezygotic mating barriers have been described in this species: a) differential host plant choice [1923], b) strain-specific timing of mating in the night [15, 16], and c) female sex pheromone differences [24–26]. Recent studies have shown that host preference in the field is not as specific as previously thought [2729]. Therefore, habitat isolation seems to be a relatively weak prezygotic mating barrier.…”
Section: Introductionmentioning
confidence: 99%